DEVELOPMENT OF FOLKLORE-BASED TIERED BOOK MEDIA TO INCREASE THE FOURTH-GRADE ELEMENTARY STUDENTS’ READING INTEREST - Anjas Kesuma; Muhammad Anizar Bayhaqi; Nursyafiq (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper reports the results in the form of a tiered book media based on folklore as a learning medium to increase the fourth-grade elementary students' interest on reading. The type of research is research and development (R&D). The developmental model used refers to the research model developed by Borg and Gall. The steps taken are problem and potential, data collection, product design, validation of design, revision of the design, product trials, product revisions, and mass production. The research subjects were fourth-grade students at SDN 74/X Bangun Karya East Tanjung Jabung Regency in Jambi. Folklore-based tiered book media products were assessed as valid by media experts with a percentage score of 77.1%. From the material expert, the percentage score was 90.9%. based on the Linguist’s validation, the percentage score was 84%. The percentage score of 4 students in the small group trial was 93.75% and the percentage score of 8 students in the large group trial was of 87.81%. Based on the analysis of differences between students' reading interests before applying the folklore-based tiered book media (Pre-test) and after applying the folklore-based tiered book media (Post-test) with an independent t-test, the value of Sig. (2-tailed) was 0.00 < 0.05. Hence, Ha was accepted, and Ho was rejected. It can be inferred that students' reading interest after applying the folklore-based tiered book media was significantly higher with an average score of 53.6250. If it was compared to students' reading interest before applying the folklore-based tiered book media, which was only 26.7500.